Can I be pregnant? – Diagnostic challenges in ruptured chronic ectopic pregnancy - Bhasyani Nagaretnam; Shamsuriani Md Jamal; Ng, BK; Janisha SR (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Ectopic pregnancy is an obstetric emergency which accounts for 4% of all pregnancy-related deaths. All women of child bearing age with abdominal pain or vaginal bleeding presenting to the Emergency Department should be evaluated forectopic pregnancy. However, there have been many reported cases of diagnostic challenges of ectopic pregnancy. One rare variant of ectopic pregnancy that can be easily overlooked is chronic ectopic pregnancy. We present this case of a 39-year-old female, who presented with acute abdomen and free fluid in her abdomen. Urine pregnancy test indicated she was not pregnant. However, intraoperative findings confirmed left tubular pregnancy. We would like to highlight three major diagnostic challenges we faced in this case i.e.; (i) women of child bearing age with abdominal pain should always be evaluated for ectopic pregnancy; (ii) diagnosis of ectopic pregnancy should not be dismissed even though the pregnancy test is negative; and (iii) the role of computed tomography (CT) scan in acute abdomen of unclear aetiology. As a rule, all haemodynamically unstable acute abdomen should be sent to the operation theatre. Haemodynamically stable patients should be carefully evaluated to facilitate surgical management.